A Multiple‐Stimulus‐Responsive Biomimetic Assembly Based on a Polyisocyanopeptide and Conjugated Polymer. Issue 22 (27th October 2017) - Meng, Fanfan; Xing, Chengfen; Yuan, Hongbo; Fan, Yibing; Chai, Ran; Zhan, Yong
Abstract: An assembly was fabricated and was revealed to be a multiple‐stimulus‐responsive biomimetic hybrid polymer architecture. It was constructed by the hydrophobic interactions between a conjugated polyfluorene that contained 2, 1, 3‐benzothiadiazole units (PFBT) and a tri(ethylene glycol)‐functionalized polyisocyanopeptide (3OEG‐PIC). The introduction of PFBT to the polyisocyanopeptide (PIC) network allowed for the incorporation of responsiveness to multiple stimuli including temperature, CO2, carbonic anhydrase, and nonlinear mechanics, which mimics natural processes and interactions. Furthermore, the light‐harvesting and signal amplification characteristics of PFBT endowed the supramolecular assembly with the essential function of fluorescence monitoring for biological processes. Abstract : Stimulating discussion : A multiple‐stimulus‐responsive supramolecular assembly (SA) was constructed by combining a conjugated polymer with a tri(ethylene glycol)‐functionalized polyisocyanopeptide (see figure). The SA exhibited responsiveness to temperature, CO2, carbonic anhydrase, and nonlinear mechanics, thus making it an excellent candidate for synthetic mimics of semi‐flexible biopolymer architectures.